The Importance and Challenges of Research and Publishing in Occupational Health During COVID-19 Pandemic - Mikhael Yosia; Ray Wagiu Basrowi (The Indonesian Journal of Community and Occupational Medicine, 2021)
Nearing the end of the second year of the COVID-19 pandemic, businesses and companies had decided to continue their operations and strive forwards, posing superfluous challenges to occupational health (OH) professionals in keeping workers safe against the continuous threat of infections. The novelty of COVID-19 results in a myriad of medical questions, all of which needs to be answered promptly and reliably through medical research followed by dissemination of answer through publications. Making the knowledge accessible through publications ensures that OH professionals and other relevant parties can collectively develop new policies, determine preventive action, the standard of procedures and care, and administer medical procedures – all of which eases the fight against pandemics in the workplace. Despite its complications and challenges, the author hoped that OH professionals realized the importance of research and publishing in the fight against this pandemic.